Wayang Kulit as a Media to Support Javanese and Indonesian Languages - Nurhalizah Alfun Sifa Harahap; Khairatul Munawarah; Esi Audya Usaida; Puja Paradilla Nasution (Departement of Mathematics Education, 2023)
Wayang Kulit is Indonesian cultural heritage that has been recognized worldwide and awarded by UNESCO in 2003. Wayang Kulit emerged in East Java and has been translated into various languages ​​since then. It greatly supported Javanese and Bahasa developement. Wayang kulit performances are very popular abroad, making it easier for the language to developed. The purpose of this study is to describe that Wayang Kulit very valuable and really influence Indonesian language and culture. This study used qualitative descriptive method, the analysis provided is following the facts and can be accepted. Using a data collection technique in the form of a questionnaire, there were 16 participants from various universities in Indonesia from young to old. The participants agreed that wayang kulit is a cultural heritage and can support the development of Javanese and Indonesian languages.